2014
DOI: 10.1186/s12884-014-0378-y
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of gestational diabetes mellitus and complimentary qualitative research: background, aims and design

Abstract: BackgroundWomen with gestational diabetes mellitus (GDM) and their offsprings are at increased risk of future type 2 diabetes and metabolic abnormalities. Early diagnosis and proper management of GDM, as well as, postpartum follow-up and preventive care is expected to reduce this risk. However, no large scale prospective studies have been done particularly from the developing world on this aspect. The objective of this study is to identify and follow a cohort of pregnant women with and without GDM and their of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…The study was carried out in two areas of TN: Chennai city and Thiruvallur district representing two different settings for GDM screening: a private urban and a government rural centre [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out in two areas of TN: Chennai city and Thiruvallur district representing two different settings for GDM screening: a private urban and a government rural centre [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The recently published literature suggests that research efforts are expanding their focus. There is a greater awareness of the contribution of chronic conditions and indirect causes of mortality to the burden of ill health experienced by women, most notably the contribution of diabetes . Researchers have started documenting economic and social consequences of maternal morbidity, and their relationship with productivity, economic growth, and development .…”
Section: Why a New Conceptual Framework?mentioning
confidence: 99%
“…There is a greater awareness of the contribution of chronic conditions and indirect causes of mortality to the burden of ill health experienced by women, most notably the contribution of diabetes. 17 Researchers have started documenting economic and social consequences of maternal morbidity, and their relationship with productivity, economic growth, and development. 18 A recent paper, fittingly entitled "Minor ailments in pregnancy are not a minor concern for pregnant women" has shown that nine out of 10 women disclosed at least one episode of ill health during pregnancy in Sri Lanka and that 60% of women could not do their day-to-day and work-related activities because of ill health.…”
Section: Mostmentioning
confidence: 99%
“…Adherence rates equal to or exceeding 80% are vital for effective control of blood glucose in diabetes mellitus [7]. Poor adherence to diet in diabetes in pregnancy has been cited in literature by a number of authors [5,[8][9][10][11]. Sousa et al reported sub-optimal adherence to diet in GDM [12].…”
Section: Adherence To Medicationsmentioning
confidence: 99%